Strength and Stiffness Behavior of Earthquake Resistant Pedestrian LVL Timber Bridge - Bernardinus Herbudiman; Delima Delima; Yosafat Aji Pranata (Masyarakat Peneliti Kayu Indonesia, 2020)
A bridge is a structure which is used to connect two areas separate by obstacles. The environmental damage caused a number of reductions in the production of timber, and by that, the LVL timber which is a high quality processed or engineered timber is chosen. This research determined the design of the timber bridge structure for pedestrian with simple beam type and earthquake resistant. The load in this bridge is referring to the SNI 1725:2016 and SNI 2833:2008, the design of the girder and the connection is referring to SNI 7973:2013, and the deflection is referring to the LFRD for Highway Bridge Superstructures. The timber bridge is designed to have a span of 10 metres long and 3 metres wide. The modeling and designing of the wooden bridge are using an application called SAP2000 based on finite element analysis. Result obtained from this research indicated that the longitudinal dimension of the girder is 360 mm x 630 mm and the cross sectional dimension is 180 mm x 270 mm. The number of bolts and lock screws needed on the connection among the longitudinal girders are 40 pieces, between the longitudinal girders and the cross sectional girders is three pieces, and between the railing and the slab are two pieces. Based on the stiffness review, the results showed that the bridge deflection that occurred was lower than the permit deflection